Centrifuge modelling and analytical solutions for the cone penetration test in layered soils - Mo, Pin-Qiang (2014)
The interpretation of measurements from the cone penetration test is still predominately based on empirical correlations, which can be attributed to the lack of understanding of penetration mechanisms, that involve severe stress-strain and shear dilatancy close to the probe. Even so, it remains one of the most widely used in-situ tools for site characterisation, and several methods for displacement pile design have been developed using CPT data. This research investigates the response of penetrometers and the behaviour of layered soils during installation of probes using geotechnical centrifuge modelling and cavity expansion analysis.